1977
DOI: 10.1071/bi9770229
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Follicular Growth and Atresia in the Ovine Ovary

Abstract: The ovaries of 21 2-year-old Merino ewes at various stages of the oestrous cycle were serially sectioned and all follicles > 0·5 mm in diameter were counted and measured. The mean number of normal follicles > 0·5 mm in diameter was 19· 9 per ewe, of which 8·7 were > 1 mm in diameter. The mean numbers of follicles > 0·5 mm in diameter in 'early', 'advanced' and 'late' stages of atresia were 4· 6, 9· 0 and 12· 3 respectively. Early atresia was rarely seen in follicles < 1 mm in diameter; the greatest incidence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
91
0
12

Year Published

1978
1978
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(122 citation statements)
references
References 22 publications
19
91
0
12
Order By: Relevance
“…Thus, continuous follicular growth occurs in the pony mare in average physical condition in the middle of the breeding season, and one hormonally priveleged period is evident towards the end of luteal phase, as in cows (Marion and Gier, 1971 ;Mariana and Nguyen Huy, 1973), ewes (Turnbull, Braden and Mattner, 1977 ;Cahill et al, 1979) and women (Gougeon, 1979). A similar conclusion was reached by Wesson and Ginther (1981) …”
supporting
confidence: 56%
“…Thus, continuous follicular growth occurs in the pony mare in average physical condition in the middle of the breeding season, and one hormonally priveleged period is evident towards the end of luteal phase, as in cows (Marion and Gier, 1971 ;Mariana and Nguyen Huy, 1973), ewes (Turnbull, Braden and Mattner, 1977 ;Cahill et al, 1979) and women (Gougeon, 1979). A similar conclusion was reached by Wesson and Ginther (1981) …”
supporting
confidence: 56%
“…Many studies have been done in order to describe the oocyte and follicular structure of several domestic species, including sheep (Turnbull et al, 1977, Cran et al, 1980and Cahill and Mauléon, 1981, goats (Lucci et al, 2001), cats (Jewgenow and Göritz, 1995), dogs (Durrant et al, 1998), pigs (Greenwald and Moor, 1989) and cattle (Hulshof et al, 1994, Beckers et al, 1996and Van Wezel and Rodgers, 1996Fair et al, 1997a andFair et al, 1997b;Hyttel et al, 1997). These studies have shown that many characteristics are similar among species, but others may differ.…”
Section: Introductionmentioning
confidence: 99%
“…These data are interesting, but we do not know the exact mitotic time (the time during which a mitotic figure is visible) of human granulosa cells. Some results on other species are available, but the values given are sometimes contradictory : 30 min (Lushbaugh, 1956), 26 min (Turnbull et al,1977) …”
Section: Introductionmentioning
confidence: 99%